2000
DOI: 10.1021/ac0008690
|View full text |Cite
|
Sign up to set email alerts
|

Control of Flow Direction in Microfluidic Devices with Polyelectrolyte Multilayers

Abstract: Electroosmotic flow (EOF) is commonly utilized in microfluidics. Because the direction of the EOF can be determined by the substrate surface charge, control of the surface chemical state offers the potential, in addition to voltage control, to direct the flow in microfluidic devices. We report the use of polyelectrolyte multilayers (PEMs) to alter the surface charge and control the direction of flow in polystyrene and acrylic microfluidic devices. Relatively complex flow patterns with simple arrangements of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
161
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(164 citation statements)
references
References 18 publications
2
161
0
1
Order By: Relevance
“…To stabilize the EOF, it has been proposed to control the pH of the eluent, or to fix the zeta potential of the capillary either by chemical modification or by adsorption. In the latter case, adsorption of polyelectrolytes is rather an easy route to achieve this goal [6][7][8][9][10]. Except for modulating the EOF, these adsorption methods, both covalent and noncovalent, have also been used to prevent nonspecific adsorption, or as a means to attach active molecules (such as antibodies) to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…To stabilize the EOF, it has been proposed to control the pH of the eluent, or to fix the zeta potential of the capillary either by chemical modification or by adsorption. In the latter case, adsorption of polyelectrolytes is rather an easy route to achieve this goal [6][7][8][9][10]. Except for modulating the EOF, these adsorption methods, both covalent and noncovalent, have also been used to prevent nonspecific adsorption, or as a means to attach active molecules (such as antibodies) to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Kenis et al demonstrated inchannel surface patterning as small as 5 m using selective etching, surface reactions, and precipitation controlled by "fabrication using laminar flow", which the authors called FLO. 53 The FLO method is suitable for a wide range of chemical treatments, including polyelectrolyte adsorption, 54,55 various organic SAMs, 26 and inorganics. 33 Zhao et al used streams of octadecyltrichlorosilane ͑OTS͒ in an organic solvent and OTS-free streams to pattern glass microchannels with hydrophobic stripes, as shown in Fig.…”
Section: A Laminar Flow and Capillaritymentioning
confidence: 99%
“…Barker et al [41] used flow imaging to obtain a more precise characterization than that obtained by current-monitoring measurement in [42]. They imaged the flow in a PMMA channel half coated with bilayer PELs and half coated with a three-layer PELs in the channel direction.…”
Section: Spatially Resolved Eof Measurementsmentioning
confidence: 99%